2023
DOI: 10.1007/s11357-023-00831-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cognitive performance differences in older age from multimodal neuroimaging data

Abstract: Differences in brain structure and functional and structural network architecture have been found to partly explain cognitive performance differences in older ages. Thus, they may serve as potential markers for these differences. Initial unimodal studies, however, have reported mixed prediction results of selective cognitive variables based on these brain features using machine learning (ML). Thus, the aim of the current study was to investigate the general validity of cognitive performance prediction from ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
1
0
0
Order By: Relevance
“…prediction of fluid intelligence. Kra ¨mer et al [39] reported a similar outcome to this study for a small trend for a multimodal benefit therefore concluded that developing a biomarker for cognitive aging remained challenging. Their study employed multimodal information, i.e., region-wise grey matter volume (GMV), resting-state functional connectivity (RSFC), and structural connectivity (SC), and generalized results across different ML approaches in 594 healthy older adults (age range: 55-85 years) from the 1000BRAINS dataset.…”
Section: Plos Onesupporting
confidence: 77%
“…prediction of fluid intelligence. Kra ¨mer et al [39] reported a similar outcome to this study for a small trend for a multimodal benefit therefore concluded that developing a biomarker for cognitive aging remained challenging. Their study employed multimodal information, i.e., region-wise grey matter volume (GMV), resting-state functional connectivity (RSFC), and structural connectivity (SC), and generalized results across different ML approaches in 594 healthy older adults (age range: 55-85 years) from the 1000BRAINS dataset.…”
Section: Plos Onesupporting
confidence: 77%
“…A possible explanation for these findings is the lack of a common link between brain structure and sleep quality/depressive symptoms, as highlighted previously ( Olfati et al, 2024 ; Weihs et al, 2023 ; Winter et al, 2024 ). Similarly, literature assessing the combined effects of brain and behavioural information found no improvement, or even a decrease, in predictability when compared to using only phenotypic information ( Dadi et al, 2021 ; Krämer et al, 2023 ; Olfati et al, 2024 ; Omidvarnia et al, 2023 ). In our study, this is consistent with the results of the HCP Young sample, where the behavioural rCCA model showed the strongest associations to MP and the addition of GMV did not increase the canonical correlation.…”
Section: Discussionmentioning
confidence: 97%
“…Functional connectivity refers to the temporal correlation of neural activity between different brain regions, which reflects the coordination and integration of neural networks. Disruptions in functional connectivity with aging [376] have been implicated in various cognitive impairments and neurological disorders [377][378][379][380][381][382][383][384][385][386][387][388]. Brain connectivity, essential for efficient cognitive function, can be influenced by dietary factors [389][390][391].…”
Section: Methionine-rich Diet Hyperhomocysteinemia and Altered Functi...mentioning
confidence: 99%